Analisis struktur, perilaku, dan kinerja pasar dalam sistem pemasaran garam rakyat di Desa Pangarengan - Moh. Ofar; Septian Eko Haryansyah; Rosi Efendi (Nur Science Institute, 2026)
This study aims to analyze the marketing of folk salt in Aengsareh Village, Sampang District, Sampang Regency. The primary focus of the research is to identify the forms of marketing channels, market structure, market behavior through vertical price integration, and market performance. The research employed both qualitative and quantitative methods, using Multistage and Snowball Sampling for data collection. The results indicate that there are two types of marketing channel patterns in the area: one-level and two-level channels. The market structure for salt at both the farmer and middleman levels tends toward imperfect competition, specifically a monopolistic market. Based on the vertical market integration analysis, it was found that perfect price integration between the farmer and processing plant levels does not occur for all salt qualities (Qualities 1, 2, and 3). This condition is attributed to the government's minimal role in price supervision and to limited access to market information for salt farmers. Market performance analysis shows that the existing marketing channels are logical and profitable for marketing institutions, as the profit share exceeds the cost share. However, the largest distribution of marketing margins and profit shares is enjoyed by the factory-level marketing institutions, while salt farmers receive a relatively small price share.